Transforming Essential Hindu Religious Materials Using Cartoon Media to Enhance the Social Skills of Students with Disabilities - Saridewi, Desak Putu; Aungsuroch, Yupin; Juanamasta, I Gede; Ariyanti, Nyoman Asti (Universitas Pendidikan Ganesha, 2025)
Students with disabilities face challenges in learning, particularly due to the limited use of instructional media and low social skills, including politeness, empathy, self-confidence, and social awareness. This study aims to transform essential materials (sacred days, holy figures, sacred places) using cartoon-based media to address issues such as multi-grade teaching and students' suboptimal social skills, which are categorized as poor. A qualitative approach was employed, utilizing observation, interviews, and documentation as methods. A total 40 students with special needs were participated. The findings indicate that integrating cartoon-based media in teaching, combined with humanistic strategies, methods, and approaches, effectively bridges the gap for students with disabilities, enabling them to develop social skills such as politeness, empathy, self-confidence, and social awareness. However, challenges arise from the continuous use of cartoon media, which can lead to monotony. To overcome these obstacles, teachers employed strategies such as incorporating ice-breaking activities, simple mindfulness-based yoga exercises, singing, and watching cartoons depicting religious celebrations. Innovative multimedia-based teaching methods, individualized instruction, and a human-centered paradigm shift were shown to significantly enhance the abilities of students with special needs. The findings imply that the use of instructional media can ease the burden on teachers, particularly those with limited sign language skills, while increasing student engagement and enthusiasm for learning. In conclusion, students with disabilities greatly benefit from tangible objects, the use of instructional media, individual and humanistic approaches, and the development of habitual learning practices.